2018
DOI: 10.4103/jips.jips_211_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of skull anthropometry for complete denture teeth selection: A cross-sectional study

Abstract: Within the limitations of this study, the results suggest that head circumference divided by 10 can be used to select a teeth set with the resulting value as the combined mesiodistal width of six anterior teeth. This can be used as a starting point for determining the width of the anterior maxillary teeth for edentulous patients, which can be further confirmed with the esthetic appearance and with other facial measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…On the other hand, Banerjee R. et. al (2018) [8] found a very strong and statistically significant correlation in contrast to our study which was in accordance with the study of Rahamatulla et. al.…”
Section: Study Samplessupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, Banerjee R. et. al (2018) [8] found a very strong and statistically significant correlation in contrast to our study which was in accordance with the study of Rahamatulla et. al.…”
Section: Study Samplessupporting
confidence: 93%
“…[9] Various anthropometric parameters have been studied and used for determination of the size of maxillary anterior teeth. [8] The variability of human face from one another on the basis of gender, ethnicity and race is an established fact. [10] Numerous studies have reported a correlation between different facial parameters and maxillary anterior tooth size, but no studies has so far been conducted comparing all these cranial circumference with the size of social six teeth in East Indian population to our knowledge.…”
Section: Study Samplesmentioning
confidence: 99%
“…In the future, these studies have to be designed with a larger sample size and more importantly with considerations of the external validity. [ 11 ]…”
mentioning
confidence: 99%